The Spatial Analysis of Population Structure Towards Demographic Bonus in Pesisir Barat Regency of Lampung - arsita, septia (Universitas Negeri Semarang, 2025)
The demographic bonus represents a strategic development opportunity that can only be optimized when population structure is supported by adequate social, economic, and spatial readiness. In Pesisir Barat Regency, disparities in productive-age population distribution, high dependency ratios, unemployment rates, and rapid population growth remain key challenges in preparing for the demographic bonus. This study aims to spatially analyze the population structure based on key demographic indicators including population growth rate, dependency ratio, proportion of the productive-age population, and open unemployment rate. A quantitative approach was applied using spatial analysis techniques within a Geographic Information System (GIS) framework. All indicators were classified using range-based value categorization, visualized through thematic mapping, and integrated into a composite readiness index using a simple linear weighting method. The findings reveal that the population growth rate remains relatively high at 2.19%, driven by a persistently elevated birth rate. The dependency ratio reaches 49.87%, while the open unemployment rate is recorded at 4.12%, with spatial variation across districts. Despite these challenges, the productive-age population accounts for 69.5% of the total population, indicating substantial potential for harnessing the demographic bonus. These results emphasize that spatially informed population planning is essential for maximizing demographic potential while minimizing socio-economic disparities. Overall, this study highlights the significance of spatial demographic mapping as a scientific basis for formulating targeted development policies to ensure the demographic bonus translates into sustained regional progress.